Eka Aneka Vis-A-Vis Tawhid Al-Asma’ Al-Husna: An Analysis Of Uthaya Sankar’s View In His Malaiur Manikam - Mastura Abd Wahab; Wan Mohd Fazrul Azdi Wan Razali (USIM Press, 2024)
Vol. 6 No. 1 (2021): Jurnal Sains Insani